Human Thrombin and Calcium Bound Factor Xa Significantly Shorten tPA-Induced Fibrin Clot Lysis Time via Neutralization of Plasminogen Activator Inhibitor Type 1 Activity - Urano, Tetsumei; Nagai, Nobuo; Matsuura, Megumi; Ihara, Hayato; Takada, Yumiko; Takada, Akikazu (Thrombosis and Haemostasis, 1998)
Employing a fibrin clot lysis assay, we reassessed the significance of the neutralization of plasminogen activator inhibitor type 1 (PAI-1) activity by thrombin and factor-Xa in fibrinolysis. When PAI-1 enriched fibrin clots were formed using increasing concentrations of thrombin (0.1, 0.5, 1.0 IU/ml), their lysis times became shorter (43.8 ± 4.9, 25.7 ± 3.7, 13.9 ± 0.8 h respectively). Times were shortened further by either heparin (43.9 ± 11.0, 12.1 ± 2.6, 3.6 ± 0.2 h respectively) or vitronectin (17.0 ± 1.6, 1.9 ± 0.7, 0.9 ± 0.0 h respectively). Factor-Xa together with Ca++ shortened the clot lysis time further. Fibrin autography revealed that both enzymes dose dependently interfered with complex formation between tPA and PAI-1, making large amounts of tPA remaining to be free form. The mechanism seems to play a role in the coagulation associated enhancement of fibrinolysis.